‘I didn’t know where to go’ - Gama, Ana (2022)
Funding Information: The study was partially supported by Fundo para o Asilo, Migração e Integração (Ref. PT/2021/FAMI/693). Funding Information: The authors wish to thank the study participants for their contribution to the research. The authors thank Ana Rita Pedro for her assistance in revising the draft of the manuscript. The authors extend their thanks to Fundação para a Ciência e a Tecnologia for funding Research 4 COVID-19—Ref. FCT 608. A.S.M. received a grant from the Fundação para a Ciência e a Tecnologia (FCT) [UI/BD/151430/2021], for her PhD. A.G. is supported by FCT/MCTES—CEEC Individual Program Contract (CEECINST/00042/2021). Publisher Copyright: © 2022 by the authors.